A novel method for formation evaluation of undersaturated coalbed methane reservoirs using dewatering data. (1st October 2018) - Shi, Juntai; Wang, Shan; Zhang, Hong; Sun, Zheng; Hou, Chenhong; Chang, Yucui; Xu, Zhenzhen
Highlights: A new method for evaluating coalbed methane reservoir properties is proposed. The pressure propagation characteristics of vertically fractured CBM well are considered. The variable permeability can also be considered during CBM reservoir evaluation. Only water production and well bottom hole pressure at the early stage are required. The method has been successfully validated by numerical simulation and analytical model. Abstract: Accurate acquisition of reservoir properties can provide an important basis for the evaluation of coalbed methane (CBM) reservoirs. To date, there are many methods that can be utilized to estimate reservoir properties. Analyzing production data by productivity equation has attracted attention of many researchers due to its simple and convenient characteristics. However, most of the productivity analysis methods are established for non-fractured wells in conventional sandstone gas reservoirs, and have restrictive requirements on boundary conditions, that is, the dominant flow-regime is boundary-dominated flow. Some CBM reservoirs have extremely low porosity and permeability, which need hydraulic fracturing to achieve greater yields. Furthermore, the reservoir fluid flow gradually changes from single-phase water flow to gas-water two-phase flow during the production process, which can increase seepage resistance and change the form of pressure propagation. Hence, there are some limitations for conventional method of productivity analysis when applying to CBM reservoirs, and the prediction results tend to have greater deviation. In this paper, a new method for evaluating formation properties of under-saturated CBM reservoirs is proposed. The method takes into account the characteristics of pressure propagation and only requires production data in single-phase water flow stage. In addition, some CBM wells are not appropriately controlled during dewatering process resulting in stress sensitive and permeability change. For this kind of wells, this paper also puts forward the relevant method to estimate the permeability change coefficient of reservoirs. The evaluation method is applicable to reservoirs which have long single-phase water flow period without well interference during the process and the pressure does not propagate to the flow boundary in dewatering stage. Hence, the greatest advantage of the proposed method is that the reservoir properties can be easily obtained only by using the water production and well bottom hole flowing pressure data at the early production stage of CBM wells. The proposed method is verified by numerical simulation data and production data calculated by analytical method, which show that this novel method is more appropriate to apply to CBM reservoirs. It is convenient and reliable in providing basic parameters for reservoir evaluation and production prediction.